Ações em educação nutricional: processo de cuidado em saúde com crianças pré-escolares da Creche Universitária - Azeredo, Elizabeth Azevedo de (2012)
Objective: Discuss nutritional educative actions implemented with pre-school children in university children ´s thought, identify if changes occur in the acceptance by preschool children of healthy food, in the view of the responsible and teachers of the study unit, having in view educative actions applied and describe the perception of preschool children´ s responsible and of teachers about these actions. Method: Study with qualitative, descriptive approach, using Focal Group technique. Population selected for the research will be composed of teachers and the responsible by preschool children of Day care children of Universidade Federal Fluminense submitted to educative actions related to healthy food implemented by Nutrition Service. For collected data analysis the content analysis according to Bardin will be used. Data that could result from content analysis will be confronted with Vygotski´s thought related to teaching-learning process.